2020
DOI: 10.2147/ott.s256918
|View full text |Cite
|
Sign up to set email alerts
|

<p>TRPV4 Overexpression Promotes Metastasis Through Epithelial–Mesenchymal Transition in Gastric Cancer and Correlates with Poor Prognosis</p>

Abstract: Transient receptor potential vanilloid 4 (TRPV4) has been reported to be involved in the progression of several human tumors. Nevertheless, clinical significance and molecular mechanism of TRPV4 in gastric cancer (GC) remain poorly defined. Patients and Methods: Immunohistochemistry assays were used to investigate the correlation between the expression of TRPV4 and epithelial-mesenchymal transition (EMT) markers in human GC tissues. The correlations between TRPV4 expression and clinicopathological features and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Huang et al activated TRPV4 in esophageal SCC, which resulted in cellular migration of the tumor cells [ 30 ]. Additionally, in gastric cancer TRPV4 is upregulated and is even associated with higher tumor invasion, lymph node metastasis and poor survival [ 31 ]. Contradictory to our results, another research group detected a downregulation of TRPV4 in specific NMSC, as Bowen’s disease (BD), solar keratosis (SK), and also BCC and SCC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al activated TRPV4 in esophageal SCC, which resulted in cellular migration of the tumor cells [ 30 ]. Additionally, in gastric cancer TRPV4 is upregulated and is even associated with higher tumor invasion, lymph node metastasis and poor survival [ 31 ]. Contradictory to our results, another research group detected a downregulation of TRPV4 in specific NMSC, as Bowen’s disease (BD), solar keratosis (SK), and also BCC and SCC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 In terms of its functions, EMT plays a vital role in modulating embryonic development, wound healing, cancer cell metastasis, and drug resistance. [24][25][26][27] It is worth noting that in non-small cell lung cancer (NSCLC), UBE2T enhances the degradation of FOXO1 in a ubiquitination-dependent manner, thus repressing EMT of NSCLC cells. 28 Similarly, this study found that FAST1 up-regulation led to up-regulated N-cadherin and Snail but inhibited E-cadherin and…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the functions of TRPV4 are different or even opposite in different tumors. TRPV4 plays an oncogenic role in breast cancer, endometrial cancer, gastric cancer, oral squamous cell carcinoma, and COAD [2,[9][10][11][12] and a suppressor gene role in glioma [1]. However-in many other tumor types-the function of TRPV4 remains unclear.…”
Section: Discussionmentioning
confidence: 99%